ANDROGEN RECEPTOR EXPRESSION IN TRIPLE NEGATIVE BREAST CANCER AND ITS RELATIONSHIP TO PROGNOSTIC FACTORS - Kneubil, Maximiliano Cassilha; Godoy, Alessandra Eifler Guerra; Coelho, Guilherme Portela; Pasqualotto, Fábio Firmbach; Madi, José Mauro; Brollo, Janaína (Mastology, 2017)
Objective: Triple negative breast cancer (TNBC) is a subset of tumors with an aggressive intrinsic biology, resulting in poor prognosis. Androgen receptor (AR) is currently one of the most studied biomarkers in TNBC, playing a role in the genesis and development of breast cancer. Methods: In this cross-sectional study, we retrospectively reviewed the medical records of all patients with TNBC who received care from 2012 to 2014 at a single health center in southern Brazil. Histological material from breast tumors was analyzed by immunohistochemistry for AR expression and related to age, histological grade, tumor-infiltrating lymphocytes (TILs), and Ki-67. Results: Of 34 TNBC cases identified, 23 (67.6%) were AR negative and 11 (32.4%) were AR positive. The average age of the patients was 51.9 years (range: 30–82 years). Among positive cases, AR was weakly expressed in 6 and strongly expressed in 5 cases. Most patients (n=28; 82.0%) had poorly differentiated tumors. Mean Ki-67 expression was 65.0% in AR-negative and 43.6% in AR-positive cases (p<0.05). There was a significant association between age and AR expression (p<0.005), which was associated with mean age 70.8 years in the strongly AR-positive group and 42.3 years in the weakly AR-positive group. The mean percentage of TILs was 38.6% in AR-positive and 39.1% in AR-negative cases (p=0.391). Conclusion: There was no significant association between AR expression and histological grade or TILs. AR positivity in TNBC was associated with older age and tumors with lower Ki-67 expression, indicating two subgroups with distinct phenotypes in patients with TNBC.